Environmental determinants of the incidence of stunting in the working area of the Tempino Health Centre, Mestong District, Muaro Jambi Regency, 2024 - Serly Oktiani; Rumita Ena Sari; Hendra Dhermawan Sitanggang (Lembaga Pengembangan Kinerja Dosen, 2024)
Stunting is a condition where a child's body size is not appropriate for their age. The consequences of malnutrition, infection, and poor social life can have long-term impacts, such as depression, loss of cognitive and mental functions. The prevalence of stunting in the Tempino Health Center Working Area in 2023 was 2.63%. This study aims to determine the relationship between environmental sanitation and the incidence of stunting in the Tempino Community Health Center Working Area, Mestong District, Muaro Jambi Regency This type of quantitative research with a case control design. The population was 100 and the sample size was 66 respondents with a ratio of 1: 1 taken with the Total Sampling technique. There is a significant relationship between the physical quality of clean water (P-Value = 0.000; (OR) = 12.880), household wastewater disposal system (P-Value = 0.003; (OR) = 5.714), latrine building (P-Value = 0.003; (OR) = 5.333) with the incidence of stunting. There was no association between household waste bins (P-Value = 0.573 (OR) = 0.619 (0.203-1.892), hand washing with soap (P-Value = 0.240; OR) = 0.411) with the incidence of stunting among children under five.